On the mechanism of extraction from solid bodies of cellular structure - Dyachok, Vasyl; Ilkiv, Ivan (Lviv Polytechnic Publishing House, 2013)
Adequacy of mathematical model of the extraction process of solid bodies of cellular structure (plant material) was proved with taking into account its anatomical structure, namely the presence of cellular and intercellular environment. Experimental verification of the mechanism of extracting of intracellular substance during extraction process flow was made. An order of diffusion coefficients through cellular membrane – Dc and in intercellular environment Dт was confirmed. Доведено адекватність математичної моделі процесу екстрагування твердих тіл клітинної будови (рослинна сировина), враховуючи її анатомічну будову, а саме наявність клітинного та міжклітинного середовища. Експериментально підтверджено механізм екстрагування внутрішньоклітинної речовини в процесі перебігу екстракційного процесу. Підтверджено порядок коефіцієнту дифузії через клітинну обоонку – Dc та в міжклітинному середовищі Dт.
Про механізм екстрагування із твердих тіл клітинної будови
Keywords: extraction; intracellular substance; intercellular environment; diffusion; екстракція; клітинна речовина; міжклітинний простір; дифузія